Living the ethics and morality of Islam - Unal, Ali (How to live as a Muslim series, 2009)
Suitable for those who seek to acquire an accurate knowledge of Islam, this title presents the fundamentals and different aspects of Islamic faith. It makes an effort to peel away the layers of what we think we know about Islam to reveal what Islam says about itself, and to explain the pillars of the Islamic faith